Retrospective Comparative Study for Effectiveness, Procedural Time and Radiation Exposure Between Primary Catheter Aspiration and Mechanical Thrombectomy with Stent Retriever in Ischemic Stroke. (16th November 2020) - Mathkour, Mansour H; Gouveia, Edna; Scullen, Tyler; Huang, Brendan; Gulotta, Paul; Vidal, Gabriel; Milburn, James; Valle, Edison
Abstract: INTRODUCTION: Mechanical thrombectomy (MT) for acute ischemic stroke (AIS) includes the use of direct catheter aspiration (AC) or stent retriever (ST) under fluoroscopic guidance. While both are proven to be effective treatment modalities, no studies have directly compared radiation exposure between these two techniques. METHODS: In this retrospective study, we identified 90 patients who underwent mechanical thrombectomy between January-December 2016 at our institution. There were three groups based on intervention type: aspiration catheter (AC), stent retriever (ST), and a combination (AC/ST). We measured hospital length of stay (LOS), fluoroscopy time, radiation dose, TICI score, and 90-day modified Rankin Scale (mRS-90) for clinical outcomes. ANOVA and a two-sample t-test were used for differences between and within groups, respectively. RESULTS: Of the 90 patients identified, 9 were lost to follow-up. Age means 69.2 (AC), 69.6 (ST), and 72.6 (AC/ST), P  =.74. Mean radiation doses were 7803.9 CGycm 2 (AC), 12, 856 CGycm 2 (ST), and 15, 396.8 CGycm 2 (AC/ST), P  = .003. Mean fluoroscopy times in minutes were 20.8 (AC), 41.7 (ST), and 61.2 (AC/ST), P  = .0001. Mean LOS were 10.8 (AC), 7 (ST), and 13 (AC/ST) days ( P = . 44). mRS-90 was 3.5 (AC), 2 (ST), and 4.1 (AC/ST), P = . 44. Mean TICI scores were 2b for both AC and ST, and 2a for AC/ST, P  < .0001. CONCLUSION: Our analysis suggests that AIS patients who undergo AC thrombectomy may be exposed to less radiation dosages, corresponding to shorter fluoroscopy times, compared to patients who are treated with ST or AC/ST. Device development should include the use of more effective tools, considering the lifetime radiation exposure of stroke treatment personnel.